Tradisi Ejuduaghi Dalam Mewujudkan Keluarga Sakinah: Analisis Fikih Keluarga Kontemporer Di Kecamatan Omben Madura - Hamdan Kifli; Siti Nurhayati; Husnul Yaqin (Jurnal Ragam Pengabdian, 2026)
The ejuduaghi (arranged marriage) tradition is a deeply rooted sociocultural practice in the community of Omben District, Sampang Regency, Madura. This study aims to critically analyze the implementation and underlying factors of the ejuduaghi tradition, its relevance to the realization of a sakinah family, and how contemporary Islamic legal discourse reconstructs this tradition. This research employed a qualitative-empirical field research approach. Primary data were collected through in-depth interviews with 15 informants consisting of individuals involved in ejuduaghi marriages and community leaders. The findings reveal a structural transformation of the ejuduaghi tradition from a strictly endogamous pattern toward exogamous marriages outside the extended family. The primary driving factor is parents' concern for protecting their children’s morality amid the community’s relatively low level of formal education. The study demonstrates that the ejuduaghi tradition has no direct relevance in determining the realization of a sakinah family, as marital success is primarily influenced by psychological readiness, maturity, and effective post-marital communication. Forced early marriages are more vulnerable to divorce and may undermine the protection of life (hifz al-nafs). From the perspective of ushul fiqh, ejuduaghi is classified as 'urf shahih; however, when practiced coercively, the legal maxim dar'u al-mafasid muqaddam 'ala jalbi al-masalih (averting harm takes precedence over acquiring benefits) becomes applicable. Therefore, preserving the ejuduaghi tradition requires a methodological reconstruction by redefining the role of parents from sole decision-makers to facilitators of family deliberation while ensuring the child's free consent as the primary prerequisite for marriage.